Exploring the impact of the COVID-19 lockdown on pre-reading skills among Portuguese children - Filipe, Marisa G.; Frota, Sónia (Frontiers in Education, 2023)
Although it could be expected that the COVID-19 pandemic impacted preschool children's abilities associated with later reading skills, research has not yet addressed the topic. Our study focused on the impact of the pandemic on phonological awareness (PA) and rapid automatized naming (RAN) abilities that have been shown to reliably predict later reading skills. A cohort of 82 typically developing European Portuguese children (mean age = 64.5 months, SD = 3.47), enrolled in their last year of preschool and dramatically affected by COVID-19 lockdowns, were assessed for PA and RAN skills. Compared to pre-pandemic normative data, our findings revealed lower average scores on the PA subtest (t = -10.85; p < .001; d = 1.62) and comparable average scores on the RAN task. A year later, the same group of children still exhibited lower scores on PA skills (t = 2.87; p = .005; d = 0.41). Furthermore, their word reading performance was also below the expected according to the normative pre-pandemic dataset (t = -2.69; p = .008; d = 0.29). A further comparison between the preschoolers affected by the pandemic and a post-pandemic cohort from the same school setting (N = 25; mean age = 72.08 months, SD = 3.30) highlighted that the pandemic cohort had lower PA average scores than their post-pandemic peers (t = 12.27; p < .001; d = 2.66). These findings underscore the enduring impact of disrupted learning environments on pre-reading abilities among preschoolers. Consequently, they contribute to further the understanding of the effects of the pandemic on the learning progress of young children.